MEMBANGUN TAMPILAN IKLAN TELEVISI DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Shafrani, Yoiz Shofwa (Fakultas Dakwah IAIN Purwokerto, 2012)
Every competitive company faces a challenge of how to get the best way to seize andmaintain the market share. Applying the promotion strategy such as advertisement is onesolution. In contemporary marketing, the existence of advertisement is to create the requirementof the product in customer’s mind.In fact, there are many violations of advertisement ethics in general which are related tobusiness competition or to the real function of an advertisement itself as a procuct information.There is a kind of formula for advertising from Islamic ethics which can be used as as an ethicalconsideration.The principles of unity, responsibility and desire in the freedom, goodness and thetruth are the principles which have to be the basic of advertisement ethics and make possible forthe advertiser to respect the truth and goodness.